The Open Data Performance Expectancy In The Transport Sector In Europe - Iwona ZDONEK (Communications of International Proceedings, 2021)
The main purpose of the paper is to describe the directions of shaping open data performance expectancy in the transport sector in Europe. There are three objectives of the paper: (1) finding the geographical areas of Europe that have a dominant contribution in creating open data performance expectancy in the transport sector; (2) finding the currently dominant terms in open data performance expectancy creation in the transport sector; (3) finding the currently dominant types of open data in the transport sector. The research methods are based on text mining analysis and visualization techniques. The analyzed data come from texts promoting digital products and services that use open data. The research covers 427 digital products and services based on open data, where 61 were dedicated to the transport sector. The time frame covers the period January 2018-January 2021 and the research focuses mainly on European issues. The research results show that the Netherlands dominates the transport sector and the second active country is the United Kingdom. France, Germany, Austria, Belgium, Denmark, Estonia, Ireland, Italy, Sweden, and Switzerland are among the active countries in the transport sector. The leading role of open data types is played by geographic data and "traffic data".
Keywords: Transport; Open Data; Open Data Performance Expectancy; Text Mining.